Non‐Stationary Outcome of Alternating Hemiplegia of Childhood into Adulthood. Issue 2 (29th December 2021) - Perulli, Marco; Poole, Josephine; Di Lazzaro, Giulia; D'Ambrosio, Sasha; Silvennoinen, Katri; Zagaglia, Sara; Jiménez‐Jiménez, Diego; Battaglia, Domenica; Sisodiya, Sanjay M.; Balestrini, Simona
ABSTRACT: Background: Although described as non‐progressive, alternating hemiplegia of childhood (AHC) can display a sudden deterioration, anecdotally reported mainly in childhood. Outcome in adulthood is uncertain. Objectives: Aim of this study is to describe the long‐term follow‐up of neurological function in adults with AHC. Methods: Seven adults with AHC were included in this retrospective single‐center study. Clinical history and previous investigation data were gathered from the review of medical records. Video‐documented neurological examination was performed at the last follow‐up visit in four out of the seven reported indivisuals. Results: Over a median follow‐up of 16 years, neurological outcome and trajectories were heterogeneous. All individuals showed new neurological signs or symptoms. Three experienced a serious irreversible neurological deterioration after prolonged quadriplegic episodes and/or status epilepticus in their second or third decade. One patient died at age 29. Conclusions: This video‐series suggests that AHC in adulthood is not stationary; larger cohorts are needed to identify genotype–phenotype correlations and clinically useful outcome predictors.